American Catholic hospitals : a century of changing markets and missions - Wall, Barbra Mann (Critical issues in health and medicine., 2011)
In American Catholic Hospitals, Barbra Mann Wall chronicles changes in Catholic hospitals during the twentieth century. Wall explores the Church's struggle to safeguard its religious values. As hospital leaders reacted to increased political, economic, and societal secularization, they extended their religious principles in the areas of universal health care and adherence to the Ethical and Religious Values in Catholic Hospitals, leading to tensions between the Church, government, and society. Wall undertakes unprecedented analyses of the gendered politics of post-Second Vatican.